Gene Therapy and its Application in Dermatology - Sarkar, Tanusree (Indian J Dermatol, 2020)
Gene therapy is an experimental technique to treat genetic diseases. It is based on the introduction of nucleic acid with the help of a vector, into a diseased cell or tissue, to correct the gene expression and thus prevent, halt, or reverse a pathological process. It is a promising treatment approach for genetic diseases, inherited diseases, vaccination, cancer, immunomodulation, as well as healing of some refractory ulcers. Both viral and nonviral vectors can be used to deliver the correct gene. An ideal vector should have the ability for sustained gene expression, acceptable coding capacity, high transduction efficiency, and devoid of mutagenicity. There are different techniques of vector delivery, but these techniques are still under research for assessment of their safety and effectiveness. The major challenges of gene therapy are immunogenicity, mutagenicity, and lack of sustainable therapeutic benefit. Despite these constraints, therapeutic success was obtained in a few genetic and inherited skin diseases. Skin being the largest, superficial, easily accessible and assessable organ of the body, may be a promising target for gene therapy research in the recent future.